NSCA's essentials of sport science - French, Duncan N. (Human Kinetics, 2022)
"This book addresses every aspect of the sport scientist role; from understanding training theory and performing needs analyses, to conducting athlete monitoring and assessment, managing data and analytics, and educating and disseminating information. By sport science practitioners working with athletes in applied settings, individuals seeking to develop their knowledge and understanding of sport science, academics and researchers, and professionals exploring how their technical expertise can offer potential benefits to athletes and sporting organizations, this book presents a comprehensive insight into the application of sport science and the role of the applied sport scientist"--